Fixed Point Theorems on Nonlinear Binary Operator Equations with Applications - Baomin Qiao (Discrete Dynamics in Nature and Society)
The existence and uniqueness for solution of systems of some binary nonlinear operator equations are discussed by using cone and partial order theory and monotone iteration theory. Furthermore, error estimates for iterative sequences and some corresponding results are obtained. Finally, the applications of our results are given.